Real-world characteristics of hospitalized frail elderly patients with atrial fibrillation: can we improve the current prescription of anticoagulants? - Annoni, Giorgio (J Geriatr Cardiol, 2016)
BACKGROUND: In elderly patients, especially those older than 80 years, atrial fibrillation (AF) is associated with an almost 25% increased risk of stroke. Stroke prophylaxis with anticoagulants is therefore highly recommended. The prevalence of factors that have been associated with a lower rate of prescription and adherence to anticoagulant therapy in these patients is little known. The objective of this study was to explore the clinical characteristics of elderly subjects, with and without AF, consecutively admitted to an acute geriatric unit, discussing factors that may decrease the persistence on stroke prophylaxis therapy. We also highlight possible strategies to overcome the barriers conditioning the current underuse of oral anticoagulants in this segment of the population. METHODS: A retrospective observational study was performed on a cohort of elderly patients with and without AF admitted to the Acute Geriatric Unit of San Gerardo Hospital (Monza, Italy). RESULTS: Compared to patients without AF (n = 1216), those with AF (n = 403) had a higher Charlson Comorbidity Index (3 vs. 2, P < 0.001), number of administered drugs (4 vs. 3, P < 0.001), rate of heart failure (36.5% vs. 12%, P < 0.001) and chronic kidney disease (20.6 vs. 13.2, P < 0.001). Many patients with AF were frail (54%) or pre-frail (29%). CONCLUSIONS: Elderly patients with AF have higher rates of conditions that affect adherence to traditional anticoagulant therapy (vitamin K antagonists, VKA). New direct oral anticoagulants (DOAs) can help overcome this problem. In order to prescribe the most appropriate VKA or DOAs, with the best efficacy/safety profile and the highest compliance, a comprehensive geriatric assessment should always accompany the scores for thrombotic and hemorrhagic risk stratification.